Delfines - Arlon, Penelope; Gordon-Harris, Tory; Prevost, John F. (New York, NY : Scholastic, Inc., 2014)
Introduces the physical characteristics, habitats, life cycle, and eating habits of dolphins.
"Incluye historias de rescates"--Cover.
"Libro digital complementario gratis"--Page 4 of cover.
Keywords: Dolphins -- Juvenile literature